Grounding practice in theory: Exploring the education angle. Issue 1 (22nd October 2020) - VanScoy, Amy; Julien, Heidi; Harding, Alison
Abstract: Preparing future information professionals includes educating them about relevant theories and models. This study explores the extent to which education for information services draws on information behavior theories, models, and concepts, particularly how instructors' choices influence the integration of information behavior into their basic reference course. Building on previous research that analyzed the syllabi and readings for basic reference courses, this study used semi‐structured interviews to explore how information behavior may be integrated into courses in ways that are not visible in the syllabus and why certain theories were more likely to be presented in the course. The 17 instructors interviewed included tenure‐track faculty, lecturers, and adjuncts who integrated information behavior theories, models, and concepts to varying degrees in their courses. By showing how choices are made to integrate theories, models, and concepts in LIS courses, the study results may inform both researchers and instructors who week to bridge the theory/practice gap.